Long-term remission of microsatellite instability-high adenosquamous carcinoma in gastric antrum: a case report - Peng Zhang; Jing Yang; Yongyong Liu; Qing Zhou; Caiqiang Xue; Bin Zhang; Yumin Li (Frontiers in Oncology)
BackgroundGastric adenosquamous carcinoma (ASC) is an exceedingly rare neoplasm. Its infrequent occurrence has resulted in sparse literature on its diagnosis and management, presenting considerable challenges for clinical practice.Case presentationA 70-year-old male presented with epigastric pain and, upon gastroscopy and CT imaging, was found to have a mass in the gastric antrum. Histopathological analysis confirmed the diagnosis of adenosquamous carcinoma. Immunohistochemical staining revealed a loss of PMS2 and MLH-1 expression, while molecular analysis confirmed MLH-1 methylation, suggesting a microsatellite instability-high (MSI-H) phenotype. The PD-L1 combined positive score (CPS) was remarkably elevated at 80. Postoperatively, the patient received six cycles of oxaliplatin in conjunction with PD-1 inhibitor therapy. At the one-year follow-up, the patient remained in long-term remission, with no evidence of recurrence.ConclusionThis case underscores the potential efficacy of integrating surgery, chemotherapy, and immunotherapy in managing gastric ASC, particularly in the context of MSI-H and elevated PD-L1 expression. It further emphasizes the critical role of comprehensive molecular profiling in guiding personalized therapeutic strategies for such rare malignancies. Further research and additional case reports are imperative to establish optimal management protocols for gastric ASC and to enhance long-term outcomes.